Downhole CO2 partial pressure calculation and tubing material selection – a case study of an offshore oil field in the South China Sea. Issue 5 (2016) - Yan, Wei; Xiang, Yong; Li, Wenliang; Deng, Jingen
Abstract : Purpose: This paper aims to establish the downhole CO2 partial pressure profile calculating method and then to make an economical oil country tubular goods (OCTG) anti-corrosion design. CO2 partial pressure is the most important parameter to the oil and gas corrosion research for these wells which contain sweet gas of CO2 . However, till now, there has not been a recognized method for calculating this important value. Especially in oil well, CO2 partial pressure calculation seems more complicated. Based on Dolton partial pressure law and oil gas separation process, CO2 partial pressure profile calculating method in oil well is proposed. A case study was presented according to the new method, and two kinds of corrosion environment were determined. An experimental research was conducted on N80, 3Cr-L80 and 13Cr-L80 material. Based on the test results, 3Cr-L80 was recommended for downhole tubing. Combined with the field application practice, 3Cr-L80 was proved as a safety and economy anti-corrosion tubing material in this oil field. A proper corrosion parameter (mainly refers to CO2 partial pressure and temperature) can ensure a safety and economy downhole tubing anti-corrosion design. Design/methodology/approach: Based on Dolton partial pressure law and oil gas separation process, CO2 partial pressure profile calculating method in oil well is proposed. An experimental research was conducted on N80, 3Cr-L80 and 13Cr-L80 material. A field application practice was used. Findings: It is necessary to calculate the CO2 partial pressure properly to ensure a safety and economy downhole tubing (or casing) anti-corrosion design. Originality/value: The gas and oil separation theory and corrosion theory are combined together to give a useful method in downhole tubing anti-corrosion design method.